The Production of Lactic Acids grom Lactobacillus acidophilus - Amhar Abubakar (Jurnal Agripet, 2000)
ABSTRACT.The ratio of D-and L-lactic acid produced in media by 39 strains of the L. acidophilus group lactic acid bacteria (A1-A4,B1, and B2 subgroups) was analyzed by high performance liquid chromatography (HPLC). L. acidophilus (A1) and L. jhonsonii (B2) produced the lowest ( 5 strains average : 41.9%) contents of D-lactic acid in MRS broth, respectively. Generally, the most dominant lactic acid (more than 50%) produced by each strain in MRS broth was a D-type isomer, except for the A1 subgroup. In L. gasseri DSM 20243T (B1), increases in the sugar content in MRS broth induced both a high production of total lactic acids and a high ratio of D-lactic acid. In skim milk, D-lactic acid decreased by 20 30 % in 5 strain types of the L. acidophilus group except L. amylovorus JCM 1126 T (A3). By sequentially changing the medium, the content of D-lactic acid in the final MRS broth reverted to almost the same level of that in the initial MRS broth. These results indicated that the ratio of D-lactic acid produced by L. acidophilus group bacteria may be controlled by improving fermentative condition